Combined impacts of sea level rise and invasive species on Cordylanthus maritimus (Salt Marsh Bird's Beak) in Upper Newport Bay, California. - Hannah V Spear; Zheyuan Zhuang; Chloe Selby; Faith Nicoll; David C Bañuelas; Alys Arenas; Amanda Swanson; Elizabeth D Crook (PLoS ONE)
From Central California to Northern Baja California, Salt Marsh Bird's Beak (Cordylanthus maritimus subsp. Maritimus; C. maritimus) is an annual hemiparasitic halophyte that is endemic to coastal salt marshes and is both state and federally endangered in the US and Mexico. By the year 2100, sea level is projected to rise by nearly a meter, which will decrease the biodiversity of salt marshes and lead to changes in plant community assemblages, impacting the narrow ecological niche of C. maritimus. Here, we address how sea level rise will impact the preferred elevation range of C. maritimus, and we examine how these impacts will be compounded by the presence of an invasive perennial plant species, Algerian sea lavender (Limonium ramosissimum; L. ramossisimum). We used LiDAR data, plant distributions, and sea level rise projections for the Upper Newport Bay Ecological Reserve to create simplified species distribution models and map current and future ranges for both species, serving as a case study for future management practices along the California Coast. In our small-scale model, the areas of these ranges and the area of overlap between both species were calculated for 2020, 2050, and 2100 under varying sea level rise scenarios. Although the overlap between the two species' ranges currently exists, C. maritimus inhabits a smaller area at relatively lower elevations than L. ramosissimum. By the year 2100, we project L. ramosissimum will occupy between 200-300% more habitable area than C. maritimus. More than 98% of the projected habitable area for C. maritimus may also be suitable for L. ramosissimum, increasing competition between the two species and highlighting a critical need to strategically control invasive L. ramosissimum in Upper Newport Bay.